2018
DOI: 10.1302/1863-2548.12.170101
|View full text |Cite
|
Sign up to set email alerts
|

The natural history of spinal deformity in patients with Coffin-Lowry syndrome

Abstract: PurposeLittle is known about the natural history of spinal deformities in Coffin-Lowry syndrome (CLS). Our goal was to evaluate the spinal deformity progression and clinical impact.MethodsIn this institutional review board-approved study, we performed a multinational retrospective review of six male CLS patients, aged 13 to 22 years at final follow-up, for a mean of 7.25 years (3 to 13).ResultsAll showed delayed skeletal maturity. Three had calcifications of their lower cervical ligamentum flavum, all experien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…What is more, RSK2 out of function is related with bone mineralization abnormal and also induces spine malformations and calcifications of ligamentum flavum, such as thoracic lordosis, scoliosis, kyphosis, and degenerative disc disease (19, 20). Previous reports identified the ERK/ RSK2 as a regulator of bone formation in vivo (7).…”
Section: Discussionmentioning
confidence: 99%
“…What is more, RSK2 out of function is related with bone mineralization abnormal and also induces spine malformations and calcifications of ligamentum flavum, such as thoracic lordosis, scoliosis, kyphosis, and degenerative disc disease (19, 20). Previous reports identified the ERK/ RSK2 as a regulator of bone formation in vivo (7).…”
Section: Discussionmentioning
confidence: 99%
“…Welborn et al found in their cohort study that frequent evaluation of skeletal changes should be carried out by health providers with a lower threshold for surgical intervention to limit spinal cord compression. 6 His severe skeletal deformities with resultant anatomical flexion, rotation, and contractures created significant difficulty in visualizing where vertebral bodies begin and end, making it impossible to gauge where to draw the necessary Cobb’s angle lines. Moreover, the severity of his scoliosis led to significant difficulties with ventilation.…”
Section: Discussionmentioning
confidence: 99%